Intravaginal inoculation of mice with the Chlamydia trachomatis mouse pneumonitis biovar results in infertility. - de la Maza, L M (1994)
In an attempt to establish a model of chlamydial ascending salpingitis and infertility, three inbred strains of mice, C3H/HeN (H-2k), C57BL/6N (H-2b), and BALB/cAnN (H-2d), were inoculated intravaginally with 3 x 10(7) inclusion-forming units of the Chlamydia trachomatis mouse pneumonitis biovar. Mice mated 6 weeks following inoculation were found to have a significant decrease in fertility rate compared with the control groups, as shown by a reduction in the number of pregnant mice and a decrease in the number of embryos.